SITTING VOLLEYBALL PLAYERS: DIFFERENCES IN PHYSICAL AND PSYCHOLOGICAL CHARACTERISTICS BETWEEN NATIONAL AND LEAGUE TEAMS (Kinesiology, 2020)
The aim of the present study was to describe and compare physical profiles and certain psychologicalaspects of sitting volleyball players in a national team and in a league team. Twenty-seven Brazilian sittingvolleyball players (15 from the national team, 12 from the league team) took part in this study. They completeddemographics, FANTASTIC, anthropometrics, handgrip, seated chest pass, modified agility T, modified speedand agility, and speed and endurance tests. Data were processed by χ2-test, Mann-Whitney U test, Pearsoncorrelation, and a stepwise multiple linear regression analysis. The national team players had significantlymore training time and better lifestyle (p